Effects of probiotic supplementation on cardiovascular risk factors in hypercholesterolemia: A systematic review and meta-analysis of randomized clinical trial. (November 2020) - Jiang, Jinchi; Wu, Caie; Zhang, Chengcheng; Zhao, Jianxin; Yu, Leilei; Zhang, Hao; Narbad, Arjan; Chen, Wei; Zhai, Qixiao
Graphical abstract: Highlights: Probiotics can reduce total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels. Greater impact on TC was observed in subgroup with multiple strains than single strain. Stronger effect on LDL-C was observed in subgroup with intervention of more than 6 weeks. More effectiveness on LDL-C was observed in subgroup with higher-dosage of probiotics. Abstract: The aim of this meta-analysis was to assess the effects of probiotic consumption on the lipid profiles of hypercholesterolemic patients in randomized controlled trials (RCT). We performed systematic searches in The Cochrane Library, Web of Science, Medline and Google Scholar for relevant studies published up to March 2020. Of the 2346 reports that were screened, 13 randomized clinical trials were selected. The pooled data revealed that probiotic supplementation significantly ( p  < 0.05) decreased total cholesterol (TC) [n = 20; standardized mean difference (SMD) = −0.30; 95% confidence interval (CI): −0.43, −0.16; p  < 0.0001] and low-density lipoprotein cholesterol (LDL-C) levels (n = 20; SMD = −0.32; 95% CI: −0.46, −0.19; p  < 0.00001) in hypercholesterolemic patients. We found that the administration of probiotics counteracted some aspects of dyslipidemia in hypercholesterolemic patients.